On Integrability of Christou’s Sixth Order Solitary Wave Equations - Allami, M. (Iraqi Journal of Science, 2019)
We examine the integrability in terms of Painlevè analysis for several models of higher order nonlinear solitary wave equations which were recently derived by Christou. Our results point out that these equations do not possess Painlevè property and fail the Painlevè test for some special values of the coefficients; and that indicates a non-integrability criteria of the equations by means of the Painlevè integrability.